Mengurai Diskriminasi terhadap Wanita Berhijab Syar’i: Perspekstif Nilai Kemanusiaan - Rahayu Fuji Astuti; Sofiah Aini (AN NUR: Jurnal Studi Islam, 2024)
The use of the hijab by Muslim women has experienced rapid growth in recent years, marked by increasing interest and a variety of models that follow modern fashion trends. However, the popularity of the hijab as a fashion trend also has a negative impact in the form of discrimination against women who wear the Islamic hijab. The aim of this analysis is to provide a deeper understanding of the various forms of discrimination faced by women who wear the Islamic hijab, explore its impact, and suggest concrete steps from a human values ??perspective to achieve a more just and inclusive society. This research uses a qualitative descriptive method by means of interviews. From the results of this research, discrimination against women wearing the Shar'i hijab has several impacts, namely psychologically, it has an impact on mental health. Economically, the impact of difficulty finding work can cause the economy to decline. Socially, the lack of support from the surrounding environment can make it difficult for Islamic hijab users to interact. So efforts can be made to prevent discrimination from the perspective of human values ??such as human dignity and honor, equality and non-discrimination, tolerance and respect for diversity, freedom of religion and belief, justice and solidarity, human rights. Forming and maintaining human values ??certainly requires educational assistance and legal assistance. With this, it is hoped that it can play an important role in creating an ethical society and providing justice for women who wear the Sharia hijab.